Gayatri A. answered • 10/13/21

Experienced Math and Science Tutor

**f(x)=4x-2 and g(x)=2x+1**

**f(-3)/g(-5)**

So first let's find f(-3). Since f(x) = 4x-2 and we want f(-3), just plug in -3 everywhere you see x. So you would get:

f(-3) = 4(-3) - 2

f(-3) = -12 - 2

f(-3) = -14

Now, let's find g(-5). Since g(x) = 2x+1 and we want g(-5), just plug in -5 everywhere you see x. So you would get:

g(-5) = 2(-5) + 1

g(-5) = -10 +1

g(-5) = -9

So to find f(-3)/g(-5) lets plug in the numbers we got for f(-3) and g(-5).

f(-3)/g(-5) = -14/-9 = 14/9